A controlled evaluation of monthly maintenance Interpersonal Psychotherapy in late-life depression with varying levels of cognitive function - Carreira, Kristen (2008)
OBJECTIVE: To evaluate the effect of maintenance Interpersonal Psychotherapy (IPT) on recurrence rates and time to recurrence of major depression in elderly patients with varying levels of cognitive function. METHODS/DESIGN: Two-year maintenance study of monthly maintenance IPT vs supportive clinical management (CM) in remitted depressed elderly who were participants in a previously reported placebo-controlled study of maintenance paroxetine and IPT (Reynolds et al., 2006). We used Cox regression analysis to test interactions between cognitive status (Dementia Rating Scale score) and treatment (IPT, CM) with respect to recurrence of major depression. RESULTS: We observed a significant interaction between cognitive status and treatment: lower cognitive performance was associated with longer time to recurrence in IPT than in CM (58 weeks vs 17 weeks) (HR = 1.41 [95% CI=1.04, 1.91], p = 0.03). Subjects with average cognitive performance showed no effect of maintenance IPT vs CM on time to recurrence (38 vs 32 weeks, respectively). CONCLUSION: Monthly maintenance IPT confers protection against recurrence of major depression in elders with lower cognitive functioning.